2021
DOI: 10.1002/ppul.25765
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric asthma symptom control during lockdown for the COVID‐19 pandemic in Spring 2020: A prospective community‐based study in Cyprus and Greece

Abstract: Objectives To prospectively quantify at the community level changes in asthma symptom control and other morbidity indices, among asthmatic schoolchildren in response to coronavirus disease 2019 (COVID‐19) lockdown measures. Methods In Spring 2019 and Spring 2020, we prospectively assessed monthly changes in pediatric asthma control test (c‐ACT), asthma medication usage, infections and unscheduled visits for asthma among schoolchildren with active asthma in Cyprus and Greece. We compared asthma symptom control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…Our study focuses on ED presentations that are reflective of acute asthma exacerbations, and outpatient asthma activity including patient adherence is beyond the scope of our data. However, recent reports indicate that outpatient encounters for asthma and steroid prescriptions declined during COVID lockdown, while self-reported symptom control improved (Rensing et al, 2001; Ferraro et al, 2021; Salciccioli et al, 2021; Shah et al, 2021; Kouis et al, 2022). Therefore, it is unlikely that the loss of seasonality we observed in ED visits for asthma reflects a shifting of clinical activity to an alternative setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our study focuses on ED presentations that are reflective of acute asthma exacerbations, and outpatient asthma activity including patient adherence is beyond the scope of our data. However, recent reports indicate that outpatient encounters for asthma and steroid prescriptions declined during COVID lockdown, while self-reported symptom control improved (Rensing et al, 2001; Ferraro et al, 2021; Salciccioli et al, 2021; Shah et al, 2021; Kouis et al, 2022). Therefore, it is unlikely that the loss of seasonality we observed in ED visits for asthma reflects a shifting of clinical activity to an alternative setting.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 66 , 72 , 73 , 74 , 75 , 76 , 77 , 78 Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease. 52 Despite strong associations of lockdown measures and improvements in allergic children, anxiety levels and perceptions of elevated health risk were increased among carers, 79 regardless of the actual health state of the child. 61 Although increased levels of anxiety at the time of pandemic were described in the general population, particularly fuelled by the infodemic, 80 , 81 some studies reported higher anxiety and poor health‐related quality of life in mothers of allergic children.…”
Section: Pandemic Impact On Patient Care and Mitigation Strategiesmentioning
confidence: 99%
“…Nonpharmaceutical interventions, such as handwashing, masks, and social/physical distancing, reduction in the concentrations of traffic‐related air pollutants 54,55 and decline in other respiratory infections incidence, may have contributed to reduced impact on allergic disease 56,57 particularly respiratory, 58–63 number of exacerbations 59,62,64–71 and the odds of emergency room visit and/or hospital admissions 59,66,72–78 . Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease 52 . Despite strong associations of lockdown measures and improvements in allergic children, anxiety levels and perceptions of elevated health risk were increased among carers, 79 regardless of the actual health state of the child 61 .…”
Section: Pandemic Impact On Patient Care and Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In concert, the activity of several inflammatory airway diseases, especially asthma and chronic obstructive pulmonary disease (COPD), diminished. 1,[5][6][7][8][9][10][11] By the spring of 2021, however, COVID-19 vaccines became widely available, attitudes toward preventative measures became less strict, and common viruses began to uptrend by May 2021. [12][13][14] Here, we report how viral rebound during the relaxation of COVID-19 precautions affected asthma and COPD exacerbations.…”
Section: Introductionmentioning
confidence: 99%